Características farmacognósticas y cuantificación espectrofotométrica de antocianinas totales del fruto de Prunus serótina. Subsp. capuli (Cav) Mc Vaugh “Capulí”. - Ocaña Ventura, Jessica Paola (2018)
The present research work was carried out with the aim of contributing to the study of the pharmacognostic characteristics and the quantification of total anthocyanins of the Prunus serótina fruit. Subsp. capuli (Cav) Mc Vaugh "Capulí". The fruits were collected from Caserío Campana, north of Cajabamba, Cajamarca Region identified in the Herbarium Truxillense of the National University of Trujillo with the record N° 58336 (HUT). The pharmacognostic characteristics were carried out according to the method of Miranda M. & Cuellar A., obtaining organoleptic characteristics such as suigeneris odor, color of the reddish black epicarp, color of the green mesocarp, sweet sour flavor and smooth and smooth texture; the macromorphological characteristics, weight 1.6937 ± 0.2910 g, length 0.904 ± 0.075 cm and width 1.067 ± 0.121 cm in dimensions, fresh condition, ovoid shape and smooth surface, this indicated that the fruit was fresh complying with the quality parameters and thus its acceptability; physicochemical characteristics such as relative humidity 21.7153 ± 0.3585%, residual humidity 6.4527 ± 0.2323%, total humidity 28.1680%, total ash 1.3914 ± 0.006%, water soluble ash 0.6977 ± 0.1443%, ash insoluble in hydrochloric acid 0.3927 ± 0.2337%, substances soluble in ethanol of 96 ° Gl 17.4454 ± 0.2640%, substances soluble in ethanol of 70 ° Gl, 16.8035 ± 0.7730, substances soluble in ethanol of 50º Gl 16.0179 ± 0.3120, and water soluble substances 5.7206 ± 0.6862, were within the allowable range according to the pharmacopoeias; in the determination of heavy metals, concentrations of arsenic 0.1647 ± 0.015 ppm, mercury 0.0438 ± 0.005 ppm, lead 0.0032 ± 0.001 ppm and copper 0.0355 ± 0.002 ppm were obtained; in the phytochemical screening, the presence of reducing sugars, phenols, amino acids and flavonoids was identified as anthocyanidins. Likewise, the content of anthocyanins in the fruit was quantified obtaining a concentration of 10.7117 mg of cyanidin-3-glucoside / g.